The Magician's Boy - Cooper, Susan; 1935-; Riglietti, Serena (New York, 2005)
A boy who works for a magician meets familiar fairy tale characters when he is transported to the Land of Story in search of a missing puppet.
Keywords: Characters in literature; Fiction; Puppet theater; Fiction; Fairy tales; Fiction; Magicians; Puppets; Fiction